A polyhedral ionic compound composite ceramic, preparation method and application thereof, and oxonium ion activator

By excitating the composite ceramics of polyhedral ionic compounds under high voltage electrostatic electricity, the problem of difficulty in obtaining oxonium ions is solved and its important application in long-chain organic molecules decomposition and organic matter combination is realized.

CN114760743BActive Publication Date: 2025-03-28MINJI TECH SERVICE (CHONGQING) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210345037.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-02
Publication Date
2025-03-28
Estimated Expiration
2042-04-02

AI Technical Summary

Technical Problem

Oxonium ions are difficult to obtain and have a single type, resulting in limited application.

Method used

The polyhedral ionic compound composite ceramic is used to excite the ultra-low temperature plasma flow under high-pressure static electricity, and the H, O2 and H2O in the air form oxonium ions in the ultra-low temperature plasma.

Benefits of technology

It has achieved efficient acquisition of oxonium ions and brought important value to the decomposition of long-chain organic molecules and the combination of organic matter.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114760743B_ABST
    Figure CN114760743B_ABST
Patent Text Reader

Abstract

The invention discloses a polyhedral ionic compound composite ceramic, a preparation method and application thereof, and an oxonium ion exciter. The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight: 35-45 parts of alpha-alumina, 12-18 parts of ferrosoferric oxide, 8-12 parts of zirconium oxide, 8-12 parts of organic-inorganic hybrid thorium polyacid salts, 8-12 parts of calcium fluoride, and 12-18 parts of anti-fluorite compounds. The polyhedral ionic compound composite ceramic of the invention can generate an ultra-low temperature plasma flow with a very high density under the activation of high-voltage static electricity of more than 10 kV. H, O2 and H2O in the air form resonance limiting ions (oxonium ions) with air water vapor in the ultra-low temperature plasma, thereby solving the problem of difficulty in obtaining oxonium ions and bringing extremely important value and significance to the decomposition of long-chain organic molecules and the combination of organic matter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oxonium ion excitation, and in particular to a polyhedral ionic compound composite ceramic, a preparation method and application thereof, and an oxonium ion exciter. Background Art

[0002] In physical chemistry, statistical methods are used to graphically depict the distribution of electrons in the extranuclear space. Electrons exhibit a wave-particle duality; unlike macroscopic objects, they lack definite orbits and trajectories. It's impossible to predict where they will appear in the extranuclear space at any given moment; we can only observe their presence somewhere. This appears as a negatively charged cloud surrounding the nucleus, hence the name "electron cloud." In quantum mechanics, the motion of an electron is represented by a wave function Ψ(x, y, z), and its modulus squared, |Ψ|, is used to represent the electron's motion. 2 It represents the probability density of electrons appearing somewhere in the space outside the nucleus per unit volume, which is actually |Ψ| 2 Distribution in space.

[0003] In atomic chemistry and molecular chemistry, atoms and molecules are actually constantly vibrating, which means that the electron cloud is constantly changing, sometimes like this, sometimes like that. Therefore, we cannot use one formula to describe all the states of a molecule. However, the movement of electrons has a certain range, so there will be a limit state. We can use a series of resonance limit formulas to describe H + and the limit state of H2O, H3O + This structure is that the oxygen atom has contributed its own pair of lone electrons to form a bond with the hydrogen ion, so the oxygen in the structure has a positive charge.

[0004] H3O in the structure of oxonium ions + The structure of the ion determines its properties. Compared with the most active O - Ions have stronger oxidizing and reducing properties. Since oxonium ions are difficult to obtain and have a single type, their application is relatively limited. Therefore, a composite material and excitation device that can excite the formation of oxonium ions are urgently needed. Summary of the Invention

[0005] The purpose of the present invention is to provide a polyhedral ionic compound composite ceramic, a preparation method and application thereof, and an oxonium ion exciter. The polyhedral ionic compound composite ceramic can excite an ultra-low temperature plasma flow under high-voltage static electricity. H, O2 and H2O in the air can form oxonium ions in the ultra-low temperature plasma, solving the problem of difficulty in obtaining oxonium ions and bringing extremely important value and significance to the decomposition of long-chain organic molecules and the combination of organic matter.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0007] A first aspect of the present invention provides an application of a polyhedral ionic compound composite ceramic in the preparation of oxonium ions.

[0008] A second aspect of the present invention provides a method for preparing oxonium ions, the method comprising preparing oxonium ions by using high-voltage electrostatically excited polyhedral ionic compound composite ceramics;

[0009] The high-voltage electrostatic voltage is not less than 10kV.

[0010] A third aspect of the present invention provides a polyhedral ionic compound composite ceramic, wherein the polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight:

[0011] 35-45 parts of α-alumina, 12-18 parts of ferrosoferric oxide, 8-12 parts of zirconium oxide, 8-12 parts of organic-inorganic hybrid thorium polyacid salt, 8-12 parts of calcium fluoride and 12-18 parts of inverse fluorite compound.

[0012] In the present invention, Fe is added to the α-Al2O3 crystal. 3+ Afterwards, O 2- Constitute HCP structure, Al 3+ Occupies the octahedral gap, each O 2- At the same time with 4 Al 3+ To form ionic bonds, 1 / 3 of the octahedral gaps are empty. 3+ Only occupies 2 / 3 of the octahedral gap, Al 3+ The arrangement of similar ions satisfies the rule that they should be as far away as possible; the structural cell of α-Al2O3: |O A Al D O B Al E O A Al F O B Al d O A Al E O B Al F |O A Al D O B Al E …;O 2- Total = 6 × 1 / 6 + 2 × 1 / 2 + 3 × 3 + 2 × 1 / 3 × 6 + 2 = 17; Al 3+ Total = 2 × 6 = 12; the polyhedral ionic compound of the present invention has extra O - And there is always an active electron cloud.

[0013] The composite ceramics made from the above raw materials can be regarded as a polycrystal composed of crystals and grain boundaries. Therefore, the grain boundaries of the composite ceramics are of special importance. The composite ceramics are composed of a polycrystal composed of many microcrystals, and the boundaries between the grains are called grain boundaries.

[0014] Grain boundary segregation will occur in composite ceramics to varying degrees. Grain boundary segregation is not beneficial to composite ceramics. However, if the grain boundary segregation can be effectively controlled, this phenomenon can be used to improve the performance of ceramic materials. 3+ Embedded in α-Al2O3, the active electron cloud around the crystal is always maintained. The addition of organic-inorganic hybrid thorium polysalt (prepared by the method of Example 1 in patent application number 202010318434.1) can further increase the active ion density, and the number of active ions can reach 13,000~15,000e / cm 3 .

[0015] The main diffusion pathways of substances in ceramic materials include surface diffusion, grain boundary diffusion, and intragranular diffusion. Diffusion within ceramics mainly occurs at grain boundaries and within grains. Due to the special structure of grain boundaries, the diffusion rate of substances at grain boundaries is much greater than that within grains, and the grain boundary diffusion coefficient is much higher than that within grains. Grain boundaries become high-speed channels for diffusion and mass transfer. Therefore, the solid-phase reaction and sintering, grain growth, ionic conductivity of ceramics, and aging and degradation processes in the ceramic preparation process are largely controlled by the grain boundary diffusion process. The addition of zirconium oxide to the composite ceramic of the present invention, as a solid electrolyte, can promote the full diffusion of positive and negative ions in the crystal.

[0016] The grain boundary barrier is an electrostatic barrier that is generated in the grain boundaries of conductive grains due to reasons such as incomplete lattice periodicity, dense dislocations and lattice defects, the presence of impurity atoms, and the formation of heterogeneous phases. Electrons or holes must have an energy higher than the grain boundary barrier to cross the grain boundary. This is like forming an infinite number of quantum wells inside the crystal. Thorium in composite ceramics can reduce the grain boundary barrier, allowing electrons or holes to smoothly jump from one well to countless wells, resulting in a crystal circumference of 13,000 to 15,000 e / cm. 3 The number of active ions. In short, negative ions form a densely packed structure, and positive ions occupy their interstitial positions. The smaller the grain boundary barrier, the easier the ion migration is, and the greater the concentration of the active electron cloud around the crystal.

[0017] Preferably, the inverse fluorite compound is lithium oxide, sodium oxide or potassium oxide.

[0018] A fourth aspect of the present invention provides a method for preparing the polyhedral ionic compound composite ceramic, the method comprising the following steps:

[0019] (a) weighing raw materials according to parts by weight, and then ball-milling and mixing the raw materials to obtain a mixed material;

[0020] (b) vacuum granulating and molding the mixed material to obtain a blank;

[0021] (c) sintering the blank at a high temperature to obtain the polyhedral ionic compound composite ceramic.

[0022] Preferably, the material mesh size after ball milling is not less than 3000 mesh; the particle size after vacuum granulation is 0.2~0.4mm; the molding is extrusion molding, and the pressure is not less than 250Mpa / cm 2 .

[0023] Preferably, the sintering comprises keeping the temperature at 140-160° C. for 1.5-2.5 hours, then keeping the temperature at 1500-1800° C. for 3-5 hours, and then cooling the furnace to below 250° C. for 18-25 hours before being taken out of the furnace.

[0024] A fifth aspect of the present invention provides a use of the above-mentioned polyhedral ionic compound composite ceramic in the preparation of oxonium ions.

[0025] A sixth aspect of the present invention provides a polyhedral ionic compound high-voltage electrostatic oxonium ion flow energizer, the energizer comprising a metal cover with an opening at the bottom, an energy column, an electrode needle, an insulator, a metal base, and a high-voltage electrostatic generator;

[0026] The open end of the metal cover is fixed to the metal base;

[0027] The energy column is located in the metal cover and one end is fixed to the metal base, and the end of the energy column connected to the metal base is provided with a blind hole communicating with the outside world;

[0028] One end of the electrode needle is arranged in the blind hole, and the other end is exposed outside the blind hole;

[0029] The insulator is arranged at the end of the blind hole and is located between the electrode needle and the inner wall of the blind hole.

[0030] The high-voltage electrostatic generator is electrically connected to the metal cover and the electrode needle respectively.

[0031] Preferably, the metal cover and the metal base are made of iron or copper;

[0032] The metal cover is in a bell shape.

[0033] Preferably, the energy column is made of the above-mentioned polyhedral ionic compound composite ceramic;

[0034] The electrostatic voltage generated by the high-voltage electrostatic generator is not less than 10kV;

[0035] The insulator is made of epoxy resin.

[0036] Preferably, the metal cover is electrically connected to the cathode of the high-voltage electrostatic generator;

[0037] The electrode needle is electrically connected to the anode of the high-voltage electrostatic generator;

[0038] The electrode needle is made of Cr20Ni80.

[0039] Compared with the prior art, the beneficial effects of the present invention include at least:

[0040] The polyhedral ionic compound composite ceramic of the present invention can generate a very high density ultra-low temperature plasma flow under the activation of high voltage static electricity above 10kV, and the plasma density reaches 30000 / cm 3 As mentioned above, H, O2 and H2O in the air can realize the formation of oxonium ions in ultra-low temperature plasma, which solves the problem of difficulty in obtaining oxonium ions and brings extremely important value and significance to the decomposition of long-chain organic molecules and the combination of organic matter.

[0041] The polyhedral ionic compound high-voltage electrostatic oxyonium ion flow stimulator of the present invention has a simple structure. By controlling the high-voltage electrostatic generator, a large amount of ultra-low temperature plasma can be excited to form, so that H, O2 and H2O vapor in the air form oxyonium ion flow, achieving the purpose of quickly and efficiently obtaining oxyonium ion flow. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly describes the drawings required for the specific embodiments or the description of the prior art. Similar elements or parts are generally identified by similar reference numerals throughout the drawings. Elements or parts in the drawings are not necessarily drawn to scale.

[0043] Figure 1 This is a curve showing the ultra-low temperature plasma excitation of the composite ceramic material of Example 1 of the present invention under different static voltages;

[0044] Figure 2 This is a schematic structural diagram of the polyhedral ionic compound high-voltage electrostatic oxonium ion flow exciter of the present invention. DETAILED DESCRIPTION

[0045] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only used as examples and cannot be used to limit the scope of protection of the present invention.

[0046] It should be noted that, unless otherwise specified, the technical or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs. Example

[0047] 1. Polyhedral ionic compound composite ceramics

[0048] The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight:

[0049] 40 parts of α-alumina, 15 parts of ferrosoferric oxide, 10 parts of zirconium oxide, 10 parts of organic-inorganic hybrid thorium polyacid salt, 10 parts of calcium fluoride and 15 parts of an inverse fluorite compound;

[0050] The anti-fluorite compound is lithium oxide, sodium oxide or potassium oxide.

[0051] 2. Preparation Method

[0052] The preparation method of the polyhedral ionic compound composite ceramic comprises the following steps:

[0053] (a) weighing each raw material according to parts by weight, ball-milling each raw material to a particle size of not less than 3000 mesh, and mixing the raw materials to obtain a mixed material;

[0054] (b) The mixed material is subjected to vacuum granulation and extrusion molding to obtain a blank, wherein the particle size after vacuum granulation is 0.2~0.4mm; the extrusion molding pressure is 250Mpa / cm 2 ;

[0055] (c) The blank is kept at 15°C for 2 hours, then kept at 1600°C for 4 hours, and then cooled to below 250°C over 20 hours before being taken out of the furnace to obtain the above-mentioned polyhedral ionic compound composite ceramic. Example

[0056] 1. Polyhedral ionic compound composite ceramics

[0057] The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight:

[0058] 45 parts of α-alumina, 12 parts of ferrosoferric oxide, 12 parts of zirconium oxide, 8 parts of organic-inorganic hybrid thorium polyacid salt, 8 parts of calcium fluoride and 15 parts of an inverse fluorite compound;

[0059] The anti-fluorite compound is lithium oxide, sodium oxide or potassium oxide.

[0060] 2. Preparation Method

[0061] The preparation method of the polyhedral ionic compound composite ceramic comprises the following steps:

[0062] (a) weighing each raw material according to parts by weight, ball-milling each raw material to a particle size of not less than 3000 mesh, and mixing the raw materials to obtain a mixed material;

[0063] (b) The mixed material is subjected to vacuum granulation and extrusion molding to obtain a blank, wherein the particle size after vacuum granulation is 0.2~0.4mm; the extrusion molding pressure is 250Mpa / cm 2 ;

[0064] (c) The blank is kept at 15°C for 2 hours, then kept at 1600°C for 4 hours, and then cooled to below 250°C over 20 hours before being taken out of the furnace to obtain the above-mentioned polyhedral ionic compound composite ceramic. Example

[0065] 1. Polyhedral ionic compound composite ceramics

[0066] The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight:

[0067] 35 parts of α-alumina, 15 parts of ferrosoferric oxide, 8 parts of zirconium oxide, 12 parts of organic-inorganic hybrid thorium polyacid salt, 12 parts of calcium fluoride and 18 parts of an inverse fluorite compound;

[0068] The anti-fluorite compound is lithium oxide, sodium oxide or potassium oxide.

[0069] 2. Preparation Method

[0070] The preparation method of the polyhedral ionic compound composite ceramic comprises the following steps:

[0071] (a) weighing each raw material according to parts by weight, ball-milling each raw material to a particle size of not less than 3000 mesh, and mixing the raw materials to obtain a mixed material;

[0072] (b) The mixed material is subjected to vacuum granulation and extrusion molding to obtain a blank, wherein the particle size after vacuum granulation is 0.2~0.4mm; the extrusion molding pressure is 250Mpa / cm 2 ;

[0073] (c) The blank is kept at 15°C for 2 hours, then kept at 1600°C for 4 hours, and then cooled to below 250°C over 20 hours before being taken out of the furnace to obtain the above-mentioned polyhedral ionic compound composite ceramic. Example

[0074] This example is a study of the ultra-low temperature plasma flux density excited by the polyhedral ionic compound composite ceramic of Example 1 under different static voltages:

[0075] The polyhedral ionic compound composite ceramic of Example 1 was obtained, and then the DP-6010PRO portable solid negative ion detector was used to conduct an experiment on the ultra-low temperature plasma flow density of the composite ceramic under different static voltages. The experimental results are as follows: Figure 1 As shown;

[0076] Depend on Figure 1 It can be seen that the polyhedral ionic compound composite ceramic of the present invention can generate ultra-low temperature plasma with a very high density under the activation of high voltage static electricity above 10kV, and the plasma density reaches 30000e / cm 3 Above, and increases with the increase of voltage. In addition, the plasma flow temperature is 23℃, and the plasma flow action distance is 400~800mm. Example

[0077] This embodiment is a polyhedral ionic compound high-voltage electrostatic oxonium ion flow exciter, such as Figure 2 As shown, the exciter includes a metal cover 1 with an opening at the bottom, an energy column 2, an electrode needle 3, an insulator 4, a metal base 5 and a high-voltage electrostatic generator 6; wherein, an oxonium ion flow 7 is formed between the metal cover 1 and the energy column 2;

[0078] The open end of the metal cover 1 is fixed to the metal base 5;

[0079] The energy column 2 is located in the metal cover 1 and one end is fixed to the metal base 5. The end of the energy column 2 connected to the metal base 5 is provided with a blind hole communicating with the outside world;

[0080] One end of the electrode needle 3 is arranged in the blind hole, and the other end is exposed outside the blind hole;

[0081] The insulator 4 is disposed at the end of the blind hole and is located between the electrode needle 3 and the inner wall of the blind hole.

[0082] The high-voltage electrostatic generator 6 is electrically connected to the metal cover 1 and the electrode needle 3, respectively. Specifically, the metal cover 1 is electrically connected to the cathode of the high-voltage electrostatic generator 6; the electrode needle 3 is electrically connected to the anode of the high-voltage electrostatic generator 6; the electrode needle 3 is made of Cr20Ni80;

[0083] The metal cover 1 and the metal base 5 are made of copper; the metal cover 1 is bell-shaped;

[0084] The energy column 2 is made of the polyhedral ionic compound composite ceramic of Example 1;

[0085] The electrostatic voltage generated by the high-voltage electrostatic generator 6 is not less than 10kV;

[0086] The insulator 4 is made of epoxy resin.

[0087] The excitation principle of the polyhedral ionic compound high-voltage electrostatic oxonium ion current exciter of the fifth embodiment of the present invention is:

[0088] Using a high-voltage electrostatic positive field of more than 10kV, the polyhedral ionic compound composite ceramics are excited to produce a high-density active electron cloud, forming an ultra-low temperature plasma with "fourth state" properties. In this ultra-low temperature plasma, H, O2, and H2O in the air form a resonance limit ion - H3O + From the cycloaddition reaction, carbene transfer reaction and computational chemistry, it is known that under the condition of sufficient H, O2, and H2O vapor, the number of plasma in the ultra-low temperature plasma is equal to that of H3O + The number of oxonium ions (limiting form), that is, under the excitation of an electrostatic field above 10kV, can produce 30000e / cm 3 Above H3O + Therefore, if a polyhedral ionic compound composite ceramic is used to make an energy column with a larger external size, placed in a larger space, and a higher electrostatic voltage is applied, a sufficiently large high-density ultra-low temperature plasma will be formed, thereby obtaining a very valuable and large volume of H3O + Oxonium ion.

[0089] Studies have shown that the high-density ultra-low-temperature plasma obtained by the polyhedral ionic compound composite ceramic of the present invention under high-voltage static electricity activates the water in the air to obtain a hydrated proton H3O + (Oxonium ion) is a form of proton in a water-soluble system. It is a hydrogen atom that loses an electron to form a naked proton. H3O + Configuration, hybrid defects and qualitative treatment of molecular orbitals. Protons generally cannot exist alone unless they are isolated in a high vacuum. When a proton approaches another atom or molecule, it can cause the latter's electron cloud to change. The proton can act as a lone pair electron acceptor and combine with other lone pair electron donors to form stable species.

[0090] It is often simply expected to be a typical triangular stack of sp3 hybridization, with a HOH bond angle of approximately 109° and a planar triangle centered on the oxygen atom. This structure exhibits significant distortion compared to the predictions of the valence shell electron pair repulsion theory (CSEPR). Hybrid orbital theory suggests that defective hybridization can stabilize molecules by increasing orbital overlap or reducing antibonding interactions. The commonly treated integral ratio equivalent hybridization is only possible for mutually orthogonal hybrid orbitals within a given atom. Effective equivalent hybridization can only occur when the s and p orbitals of p-block elements have similar radial extensions and a significant degree of overlap. However, for high-period heavy elements in the p-block, the radii of the np and ns orbitals differ significantly, increasing the sp energy difference and making equivalent hybridization unfavorable in terms of molecular potential energy. To achieve effective hybridization, the orthogonalization requirement must be abandoned, resulting in defective hybridization. The use of non-orthogonal hybridization in heavy elements eliminates the correlation between hybridization mode and bond angle, resulting in sp non-integer hybridization ratios that lack a corresponding geometric structure. Hybridization defects weaken the stabilizing effect brought by hybridization, resulting in molecules that are less stable during hybrid bonding. This has extremely important application value and significance for the low-temperature decomposition of some long-chain organic molecules and the combination of organic matter.

[0091] In the field of environmental protection, the complex organic components in domestic waste have always been a difficult problem to deal with. Due to the low calorific value of domestic waste, incineration of waste inevitably produces dioxins. Dioxins are a class of polyhalogenated aromatic hydrocarbons with related structures and chemical properties, which mainly include PCDDs, PCDFs and dl-PCBs.

[0092] Due to the different number and position of chlorine atoms on the benzene ring skeleton of dioxins, there are 75 PCDDs, 135 PCDFs, and 209 dl-PCBs. Dioxins share similar physical and chemical properties, with an average molecular weight of 321.96, are colorless and odorless, and have high boiling and melting points of 302-305°C. They begin to decompose at 500°C and decompose 99.99% at temperatures above 850°C for more than two seconds. They are non-polar, water-insoluble, lipophilic, and chemically stable.

[0093] The amount of energy released is the amount of energy required for the oxonium ion atom to be stable. Electron affinity is the energy released when an electron is taken into the outermost shell. A high electron affinity indicates a high tendency to take electrons from the oxidized object and become stable. In other words, when the electron affinity is high, the oxidizing ability is strong. If compared within the same period, the electron affinity of the halogen elements F and Cl is extremely large, and the electron affinity of Cl is very large, at 3.617eV. It usually becomes a monovalent anion when ionized. Among the oxonium ions, the hydronium ion is H +The electron affinity (oxidizing power) of the hydronium ion is equal to that of the hydrogen ion, which is about 13.6eV. From this value, it can be said that the oxidizing power of the hydronium ion is much higher than the redox potential of the active oxygen species. + When the non-proton ion approaches the dioxin molecule, it can deform the latter's electron cloud, H3O + Non-proton ions can act as a lone pair electron acceptor and combine with other lone pair electron donors to form stable species. Even at low temperatures, dioxins will be decomposed and no longer exist or cannot be formed at all.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. Application of polyhedral ionic compound composite ceramics in the preparation of oxonium ions, characterized in that: The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight: 35-45 parts of α-alumina, 12-18 parts of ferrosoferric oxide, 8-12 parts of zirconium oxide, 8-12 parts of organic-inorganic hybrid thorium polyacid salt, 8-12 parts of calcium fluoride and 12-18 parts of an inverse fluorite compound; the inverse fluorite compound is lithium oxide, sodium oxide or potassium oxide.

2. A method for preparing an oxonium ion, characterized in that: Preparation of oxonium ions by high voltage electrostatic excitation of polyhedral ionic compound composite ceramics; The high voltage electrostatic voltage is not less than 10kV; The polyhedral ionic compound composite ceramic is prepared from the following raw materials in parts by weight: 35-45 parts of α-alumina, 12-18 parts of ferrosoferric oxide, 8-12 parts of zirconium oxide, 8-12 parts of organic-inorganic hybrid thorium polyacid salt, 8-12 parts of calcium fluoride and 12-18 parts of an inverse fluorite compound; the inverse fluorite compound is lithium oxide, sodium oxide or potassium oxide.

3. A polyhedral ionic compound composite ceramic, characterized in that: It is prepared from the following raw materials in parts by weight: 35-45 parts of α-alumina, 12-18 parts of ferrosoferric oxide, 8-12 parts of zirconium oxide, 8-12 parts of organic-inorganic hybrid thorium polyacid salt, 8-12 parts of calcium fluoride and 12-18 parts of an inverse fluorite compound; the inverse fluorite compound is lithium oxide, sodium oxide or potassium oxide.

4. The method for preparing the polyhedral ionic compound composite ceramic according to claim 3, characterized in that: The steps include: (a) weighing each raw material according to weight, and then ball-milling each raw material and mixing them to obtain a mixed material; (b) vacuum granulating and molding the mixed material to obtain a blank; (c) sintering the blank at a high temperature to obtain the polyhedral ionic compound composite ceramic.

5. The preparation method according to claim 4, characterized in that: The material mesh size after ball milling is not less than 3000 mesh; the particle size after vacuum granulation is 0.2-0.4 mm; the molding is extrusion molding, and the pressure is not less than 250Mpa / cm 2 .

6. The preparation method according to claim 4, characterized in that: The sintering comprises keeping the temperature at 140-160° C. for 1.5-2.5 hours, keeping the temperature at 1500-1800° C. for 3-5 hours, and then cooling the furnace to below 250° C. for 18-25 hours before being taken out of the furnace.

7. A polyhedral ionic compound high voltage electrostatic oxonium ion flow exciter, characterized in that: It includes a metal cover with an opening at the bottom, an energy column, an electrode needle, an insulator, a metal base and a high-voltage electrostatic generator; The open end of the metal cover is fixed on the metal base; The energy column is located in the metal cover and one end of the energy column is fixed to the metal base, and the end of the energy column connected to the metal base is provided with a blind hole communicating with the outside world; One end of the electrode needle is arranged in the blind hole, and the other end is exposed outside the blind hole; The insulator is arranged at the end of the blind hole and is located between the electrode needle and the inner wall of the blind hole; The high-voltage electrostatic generator is electrically connected to the metal cover and the electrode needle respectively; The metal cover is bell-shaped; the energy column is made of the polyhedral ionic compound composite ceramic as claimed in claim 3; The electrostatic voltage generated by the high-voltage electrostatic generator is not less than 10 kV.

8. Use of the oxonium ions excited by the exciter according to claim 7 in low-temperature degradation of organic matter.

Citation Information

Patent Citations

  • Organic-inorganic hybrid thorium polyacid salt and preparation method and application thereof

    CN111393485A

  • Polyhedral ionic compound high-voltage electrostatic oxonium ion flow exciter

    CN218124997U